Validity and Reliability of the Korean Version of the Utrecht Scale for Evaluation of Rehabilitation-Participation - Joo-Hyun Lee; Ji-Hyuk Park; Yeong Jo Kim; Sang Heon Lee; Marcel W. M. Post; Hae Yean Park (Occupational Therapy International)
This study investigated the reliability and validity of the Korean version of the Utrecht Scale for Evaluation of Rehabilitation-Participation (K-USER-P) in patients with stroke. Stroke patients participated in this study. The Utrecht Scale for Evaluation of Rehabilitation-Participation was translated from English into Korean. A total of 120 questionnaires involving the K-USER-P were distributed to rehabilitation hospitals and centers by mail. Of those, 100 questionnaires were returned and 67 were included in the final analysis after exclusion of questionnaires with insufficient responses. We analyzed the questionnaires for internal consistency, test-retest reliability, and construct validity. The results indicated that internal consistency coefficients of the frequency, restriction, and satisfaction domains were 0.69, 0.66, and 0.67, respectively. Test-retest reliability was 0.63, 0.45, and 0.71 for the three domains, respectively. Intercorrelations between the SF-12 and the London Handicap Scale were generally moderate to good. The Korean version of the Utrecht Scale for Evaluation of Rehabilitation-Participation can be used as a measure of the participation level of stroke patients in clinical practice and the local community.